Evaluation of neutron contamination in 241Am gamma-ray source. (December 2018) - Mondal, Prasanna Kumar; Sarkar, Rupa; Datta, Manas; Chatterjee, Barun Kumar
Abstract: The 241 Am gamma-ray source has a number of medical and industrial applications. In addition to the gamma-rays the source also could yield neutrons due to the ( α, xn ) reactions with other materials such as oxygen, aluminium etc. While using this source one needs to be aware of the possible unwanted exposure to neutrons and also of wrong results. We have investigated the neutron yield from a 1.85 × 10 10 Bq 241 Am source and found that the source has a neutron yield of 3350 ± 79 neutrons/s. The variation of neutron dose rate and neutron flux with distance from the source is also obtained using superheated droplet detectors. The neutron dose is found to be about two orders of magnitude lower than the gamma-ray dose. Highlights: The 241 Am gamma-ray source could yield neutrons due to the ( α, xn ) reactions with other materials. While using this source one needs to be aware of the possible unwanted exposure to neutrons and also of wrong results. The neutron yield for a 1.85 × 10 10 Bq 241 Am gamma-ray source is found to be 3350 ± 79 neutrons/s.